2011 World Nutrition Day Report in Training, Research and Clinical Ghaem Hospital in Mashhad: - Mousavi, Seyyede Neda; Dahri, Monireh; Nemati, Mohsen; Kazemi, Fatemeh; Norouzi, Abdolreza; Purafzali Firouzabadi, Seyyed Javad (Galen Medical Journal, 2013)
Introduction: Malnutrition in hospitalized patients will worsen the medical condition or disease prognosis. Also, duration of hospitalization and recovery will be delayed. In order to investigate these problems, the team of World Nutrition Day, on behalf of Nutritional Support Organization of Australia (with ESPEN support) decided to perform extensive research as a multi-centered one on the nutritional status of hospitalized patients in the world. This study aimed to compare the nutritional status of patients in the intensive care units (ICUs) of Ghaem Hospital with that in the world. Methods and Materials: This study is part of a cross-sectional multi-center audit which was held by the Nutritional Support Organization in Australia (with ESPEN support) on November 4th, 2010. From Iran, only Ghaem Hospital, with 8 ICUs, participated in this study. First, the consent form, and then questionnaires designed by the team of World Nutrition Day were filled for patients. After the completion of the questionnaires, they were sent online to the Center of Nutritional Support in Australia. Data were analyzed by the Center of Nutritional Support in Australia and were returned after they had been compared with the other centers as tables. Results: Thirty-two patients from the ICUs of Ghaem Hospital were participated in this study. Mean age was 57 years, and 46.9% of the patients were female. Parenteral feeding was not prescribed, and the total calorie intake of the patients was 394Â±790. Also, no monitoring was performed for the blood glucose of the patients, and the mean duration of hospitalization in the ICU was 19 days. Conclusions: This study shows that the presence of nutrition experts in the various units of hospitals is critical to better assess patientsâ€™ needs and to promote Iranian hospitals to reach global standards. [GMJ. 2012;1(2):84-87]